粗視化分子動力学法による水和モンモリロナイトの組織構造シミュレーション - 河村, 雄行; 木本, 和志; 牧野, 仁史 (Journal of Computer Chemistry, Japan, 2020)
This study proposes a 2D coarse-grained molecular dynamics (CGMD) method for the compaction simulation of montmorillonite clay.In the CGMD method, a unit structure of a water-hydrated clay molecule is coarse-grained into a particle.Thus, the deformable molecules are modeled as a set of linearly connected coarse-grained particles.As the inter-particle forces, the intra-molecular bonding and inter-molecular van der Waals forces are considered.For simplicity, the intra-molecular bonding is modeled as a linear harmonic oscillator, while the Lenard-Jones potential is used to define the van der Waals force field. With this model, the mechanical compaction of moistured montmorillonite is numerically simulated to find that 4-6 considerably deformed molecules are layered as a result of the compaction.It is also found that the simulated XRD pattern agrees with the experiment in terms of the peak angle.